Aquifer Security and the Place of the Aquifer in International Conflicts - Tarık Demir (Avrasya İncelemeleri Dergisi)
It is a well-established fact that water is an essential resource for human survival. Consequently, addressing issues related to water resource security and ensuring access to clean water is a top priority for both domestic and foreign policies of nations. Essentially, the availability of clean water is threatened by factors like climate change and human activities. This has led to discussions about the significance of aquifer resources, which hold abundant clean water, in the realm of international relations. Historical analysis reveals that states have often competed for control over aquifer resources in various parts of the world. This study focuses on the Brahmaputra and Guarani aquifer systems in South Asia and South America, respectively, which are among the most significant aquifer resources. By examining the foreign policy approaches of states toward these aquifer systems, it is observed that while conflicts have arisen over the Brahmaputra aquifer system, a shift toward cooperative strategies has occurred over time regarding the Guarani Aquifer System, following the principles of the Regional Security Complex Theory. The aim of this study is to explore the relationship between specific aquifer systems and the concept of conflict through qualitative research methods.